Efficacy of intraosseous local anesthesia for restorative procedures in molar incisor hypomineralization-affected teeth in children - Uma B Dixit; Amil V Joshi (Wolters Kluwer Medknow Publications, 2018)
Background: Treatment of teeth affected with molar incisor hypomineralization (MIH) in young patients is challenging due to chronic subclinical pulpal inflammation caused by porous enamel and exposed dentin. Hypersensitivity of the teeth and difficulty in achieving local anesthesia due to altered nerve potential affects the successful completion of the treatment. Aim: The aim of the study was to compare the anesthetic efficacy of the intraosseous (IO) anesthetic technique with conventional local infiltration technique in anesthetizing first permanent molars (FPMs) affected by MIH for restorative procedures in children. Materials and Methods: This randomized controlled clinical trial recruited 54 MIH-affected mandibular or maxillary FPMs requiring restorations or stainless steel crowns. The teeth were randomly allocated to two equal groups to receive either IO injection or buccal infiltration (control), both using 4% articaine. Onset, time required, and pain experienced for administration, need for repeat, efficacy of anesthetic technique, heart rate, and postoperative complications were recorded in both the groups. Collected data were subjected to statistical analysis. Results: Onset was significantly faster and pain experienced during administration was significantly lower with IO technique. Need for repeat of anesthesia was significantly more with infiltration (44.4% vs. 7.4% in IO, P = 0.004). Local infiltration failed to produce profound anesthesia in 74.1% MIH-affected teeth. IO anesthesia profoundly anesthetized 88.9% MIH-affected teeth. Anesthetic efficacy was significantly better with IO anesthesia (P < 0.001). Postoperative complications were significantly lower with IO anesthesia (P = 0.003). Conclusion: IO local anesthesia was found to be an effective and safe technique to achieve profound anesthesia in MIH-affected teeth in children in comparison to local infiltration.